2009
DOI: 10.1002/ana.21537
|View full text |Cite
|
Sign up to set email alerts
|

Medullary pain facilitating neurons mediate allodynia in headache‐related pain

Abstract: OBJECTIVE-To develop and validate a model of cutaneous allodynia triggered by dural inflammation for pain associated with headaches. To explore neural mechanisms underlying cephalic and extracephalic allodynia. METHODS-Inflammatory mediators (IM)were applied to the dura of unanesthetized rats via previously implanted cannulas and sensory thresholds of the face and hindpaws were characterized.RESULTS-IM elicited robust facial and hindpaw allodynia which peaked within 3 hr. These effects were reminiscent of cuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
216
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 180 publications
(234 citation statements)
references
References 39 publications
16
216
2
Order By: Relevance
“…These data echo the finding of CGRP antagonists and/or sumatriptan attenuated facial allodynia triggered by inflammation or NO in models of headache. 28,82 Trigeminal allodynia was not different in iNOS knockout and WT injured groups at 2 weeks, which may be explained by CGRP levels being well above control levels. In contrast, nNOS and iNOS inhibitors attenuated mechanical hypersensitivity after nerve injury.…”
Section: Trauma-induced Pain Signaling Molecules and Their Modulationmentioning
confidence: 87%
See 1 more Smart Citation
“…These data echo the finding of CGRP antagonists and/or sumatriptan attenuated facial allodynia triggered by inflammation or NO in models of headache. 28,82 Trigeminal allodynia was not different in iNOS knockout and WT injured groups at 2 weeks, which may be explained by CGRP levels being well above control levels. In contrast, nNOS and iNOS inhibitors attenuated mechanical hypersensitivity after nerve injury.…”
Section: Trauma-induced Pain Signaling Molecules and Their Modulationmentioning
confidence: 87%
“…44 Inflammation, hyperactivation, or circuit disruptions within the brain's central nociceptive pathways cannot be ruled out as a generator of PTH. 7,48,78,[80][81][82] Interactions between CGRP-and iNOS/NO-signaling pathways may converge in the thalamus eliciting photosensitivity. Neurons in the posterior thalamus respond dually to input from dural nociceptors (trigeminal ganglion cells) and photoreceptors (retinal ganglion cells) 24,83 ; this pathway is proposed to explain photosensitivity during primary and, perhaps, PTH.…”
Section: Trauma-induced Pain Signaling Molecules and Their Modulationmentioning
confidence: 99%
“…The holding temperature obviates any concern that apparent effects on reflex latency could be attributed to changes in skin temperature. Previous work has shown that response latencies and neuronal response properties are stable for a period of several hours with this testing protocol (Edelmayer et al 2009;Heinricher et al 2004Heinricher et al , 2010Kincaid et al 2006;Martenson et al 2009). …”
Section: E T H O D Smentioning
confidence: 89%
“…However, it becomes evident recently that the descending control from the brainstem is bidirectional and there is a dynamic balance between the pain inhibition and facilitation [13], which can be altered in pathological states. Brainstem alterations have been widely discovered in migraineurs [9,14,15], supporting its' modulatory function in the disease.…”
mentioning
confidence: 97%
“…The TCC and thalamus also receive projections from several nociceptive modulatory brain regions, and sensitization of neurons in the two regions has great impacts in the process of headache chronification. Also, the sensitization of TCC and thalamus is believed to be the underlying mechanisms of allodynia [8,9], a common physical sign in migraine patients, featured by increased skin sensitivity in the referred pain area and even the other side of the head or the forearm.…”
mentioning
confidence: 99%